2021
DOI: 10.3390/jdb9030035
|View full text |Cite
|
Sign up to set email alerts
|

In Utero Programming of Testicular Cancer

Abstract: It is well established that the intrauterine biological environment plays important roles in fetal development. In this review, we re-visit the hypothesis that testicular germ cell cancer (TGCC), especially in adolescents and young adults, has been programmed in utero. The origin for extreme in utero environments is mostly maternal driven and may be due to nutritional, physical and psychological stressful conditions that alter the optimal molecular and biophysical in utero environments. Moreover, precursors fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Intrauterine concentration of estrogen, which increases circa 10 times in the female and 100 times in the male fetus, may affect invalid germ cells development. Moreover unequal maternal nutrition may also induce alternations in development of fetal cells with following risk of teratogenesis in metabolic, anthropometric and behavioral functions [ 23 ]. Another study suggested that fetal programming, by decreased size of placenta in association with large birth weight (LGA) and low placenta-to-birthweight ratio, may impact to increased risk of developing Wilms tumor in the offspring [ 24 ].…”
Section: Long-term Complications Caused By Stress On Maternal and Off...mentioning
confidence: 99%
“…Intrauterine concentration of estrogen, which increases circa 10 times in the female and 100 times in the male fetus, may affect invalid germ cells development. Moreover unequal maternal nutrition may also induce alternations in development of fetal cells with following risk of teratogenesis in metabolic, anthropometric and behavioral functions [ 23 ]. Another study suggested that fetal programming, by decreased size of placenta in association with large birth weight (LGA) and low placenta-to-birthweight ratio, may impact to increased risk of developing Wilms tumor in the offspring [ 24 ].…”
Section: Long-term Complications Caused By Stress On Maternal and Off...mentioning
confidence: 99%